Dive into Inclusive Education for Children with Special Needs in Indonesia - Himamy Zahrotul Masruroh; Wiwin Hendriani (Budapest International Research and Critics University, 2022)
This study aims to qualitatively describe the empirical facts between the expectations and the reality of implementing inclusive education in Indonesia for children with special needs. The government's efforts to legitimize inclusive education for children with special needs in regular schools ranging from primary to secondary education have increasingly opened up opportunities for children with special needs to obtain quality educational services. However, good policies are not matched by the readiness of schools that are recommended to provide adequate facilities and support for learning resources. As a result, there are indications that the education of children with special needs in inclusive schools has not received educational services that match their needs. This study uses a library research design and primary and secondary sources to obtain research data. In other words, this library research limits its activities to collecting data through library collection materials (manual and internet) without the need for field research. In practice, this library research activity series relates to collecting library data, reading and taking notes, and processing research materials.